2016
DOI: 10.1016/j.xphs.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A Minireview: Usefulness of Transporter-Targeted Prodrugs in Enhancing Membrane Permeability

Abstract: Orally administered drugs are categorized into 4 classes depending on the solubility and permeability in a Biopharmaceutics Classification System. Prodrug derivatization is one of feasible approaches in modifying the physicochemical properties such as low solubility and low permeability without changing the in vivo pharmacological action of the parent drug. In this article, prodrug-targeted solute carrier (SLC) transporters were searched randomly by PubMed. Collected SLC transporters are amino acid transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 130 publications
(151 reference statements)
0
15
0
1
Order By: Relevance
“… 121 It has been found that in the intestinal cells, coronavirus increases the glucose absorption through sodium ion-dependent glucose transporters known as SGLT1. 122 In DENV infected cells, it has been successfully demonstrated that treatment of infected cells with sodium oxamate and 2-deoxy-D-glucose (2DG) results in inhibition of glycolysis and thus, in DENV replication. 123 , 124 …”
Section: Host Pathways Exploited By +Ssrna Virusesmentioning
confidence: 99%
“… 121 It has been found that in the intestinal cells, coronavirus increases the glucose absorption through sodium ion-dependent glucose transporters known as SGLT1. 122 In DENV infected cells, it has been successfully demonstrated that treatment of infected cells with sodium oxamate and 2-deoxy-D-glucose (2DG) results in inhibition of glycolysis and thus, in DENV replication. 123 , 124 …”
Section: Host Pathways Exploited By +Ssrna Virusesmentioning
confidence: 99%
“…Modifying drugs to improve their pharmacokinetic properties results in so-called prodrugs, which are generally bioreversible derivatives of the parent drug molecules that undergo an enzymatic or chemical transformation in vivo to release the active parent drug [6]. Over the past 10 years, significant effort has been made in the design of novel prodrug molecules with improved pharmacokinetic profiles [7,8]. One successful approach has been to use amino acids as promoieties, as these confer several advantages on the parent compound, including increased water solubility and the targeting of intestinal SLC transporters for oral drug delivery [9].…”
Section: Introductionmentioning
confidence: 99%
“…The test formula 600 mg sample solution-tablet, batch number S580317 In a Biopharmaceutics Classification System (BCS), orally administered drugs are categorized into four classes depending on the solubility and permeability. BCS class I drugs exhibit high solubility and high permeability, class II drugs low solubility and high permeability, class III drugs high solubility and low permeability, and class IV drugs low solubility and low permeability [85,86]. ALA is found in BSC II [25] and tested according to the USP ALA tablets Monograph.…”
mentioning
confidence: 99%